The impact of the COVID-19 pandemic on colorectal and gastric cancer diagnosis, disease stage and mortality - Abu-Freha, Naim; Hizkiya, Reut; Abu-Abed, Muhammad; Michael, Tal; Jacob, Binil Mathew; Rouvinov, Keren; Schwartz, Doron; Reshef, Avraham; Netz, Uri; Pinsk, Ilia; Etzion, Ohad (Frontiers in Medicine, 2022)
Background: Since the outbreak of COVID-19, a significant decline in endoscopic procedures has been observed. Aims: We investigated the change of incidence, clinical characteristics, disease stage and mortality of patients with gastric cancer (GC) or colorectal cancer (CRC) diagnosed in 2020 compared to the pre-pandemic year 2019. Methods: Demographic, clinical and laboratory data on all patients diagnosed with GC or CRC at the Soroka University Medical Center were retrospectively collected and compared. Number of cases, time of diagnosis, clinical presentation, staging at diagnosis and mortality rates were compared. Results: 216 patients were diagnosed with CRC in 2019, whereas only 162 were diagnosed in 2020 (25% reduction), while 36 GC diagnoses were made in 2019 compared to 24 in 2020 (33% reduction). The age-adjusted incidence was calculated to be 24.28 for CRC and 5.0 for GC in 2020 compared to 29.93 and 5.32 in 2019, respectively. CRC patients had a significantly lower rate of rectal bleeding as their presenting symptom in 2020 compared with 2019, 8.1% vs 19% (p=0.003), but higher rate of diarrhea as their presenting symptom, 4.3% vs 1% (p=0.044). No significant differences regarding other presenting symptoms, comorbidities, surgery or mortality rates were found between the groups diagnosed in 2019 or 2020. Conclusion: A decrease in GC and CRC incidence was observed during the year 2020; lower rate of rectal bleeding and higher rate of diarrhea as presenting symptoms were noted in 2020, but no significant difference was found regarding other presenting symptoms, disease stage, surgery or mortality.